2022
DOI: 10.12775/ed.2022.006
|View full text |Cite
|
Sign up to set email alerts
|

Osądzanie refleksyjne – tutorzy i tutees na temat trudnych poznawczo problemów

Abstract: Niniejszy artykuł prezentuje badania przeprowadzone w celu uzyskania odpowiedzi na pytanie, w jaki sposób tutorzy (nauczyciele akademiccy) i tutees (studenci) formują osądy na temat kilku trudnych poznawczo problemów. W badaniu skoncentrowano się na opisie intelektualnych procedur stosowanych w refleksyjnym osądzaniu tutorów i tutees. Rozstrzygano, na ile jest to myślenie na poziomie prerefleksyjnym, quasirefleksyjnym i refleksyjnym. Podczas badania tutorzy i tutees byli postawieni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The third stage (theory) relates to drawing conclusions based on the assimilated theory. By comparing experience with newly acquired knowledge, the learner (student) develops their own theories (Perkowska-Klejman, 2003).…”
Section: Learning Concepts In the Context Of E-learningmentioning
confidence: 99%
“…The third stage (theory) relates to drawing conclusions based on the assimilated theory. By comparing experience with newly acquired knowledge, the learner (student) develops their own theories (Perkowska-Klejman, 2003).…”
Section: Learning Concepts In the Context Of E-learningmentioning
confidence: 99%
“…Ten typ uczenia się i jego znaczenie dla rozwoju jednostki charakteryzuje Jack Mazirow, autor koncepcji uczenia się transformatywnego (zob. szerzej: Pleskot-Makulska, 2007;Perkowska-Klejman, 2014).…”
Section: Projektowanie Spotkań W Ramach Sieci Współpracy I Samokształ...unclassified
“…The studies on reflectivity and reflection we managed to identify in the literature focused primarily on finding answers to questions about the circumstances in which the participants of these studies showed reflectivity (or lack thereof) as well as questions about the external conditions that favored the transition from an absence of reflectivity to reflectivity (see Szymczak 2017). Additionally, we examined studies on students' reflexivity (Perkowska-Klejman 2014, 2016, 2019. We also took note of a project in which reflexivity (along with self-criticism) was one of the elements of the author's Questionnaire of Self-Assessment of Critical Dispositions (Czaja-Chudyba 2013).…”
Section: Introductionmentioning
confidence: 99%